2013
DOI: 10.1182/blood-2012-12-476101
|View full text |Cite
|
Sign up to set email alerts
|

COP1 targets C/EBPα for degradation and induces acute myeloid leukemia via Trib1

Abstract: Key Points• Ectopic COP1 decreases C/ EBPa and blocks granulocyte differentiation in 32D cells.• Trib1 binds to COP1 to enhance its ubiquitin ligase activity for C/EBPa. COP1 accelerates development of AML induced by Trib1.The ubiquitin ligase constitutively photomorphogenic 1 (COP1) is involved in many biological responses in mammalian cells, but its role in tumorigenesis remains unclear. Here we show that COP1 is a ubiquitin ligase for the tumor suppressor CCAAT/enhancer-binding protein (C/EBPa) and promotes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
85
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(88 citation statements)
references
References 32 publications
3
85
0
Order By: Relevance
“…15,16,20) In contrast, in adipocytes, TRB1 is a nuclear transcriptional co-activator for the nuclear factor κB (NF-κB) subunit RelA, thereby promoting induction of proinflammatory cytokines in these cells. 45) TRB1 is also a target of inflammatory signals, which provides a molecular rationale for the amplification of proinflammatory responses in white adipose tissue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15,16,20) In contrast, in adipocytes, TRB1 is a nuclear transcriptional co-activator for the nuclear factor κB (NF-κB) subunit RelA, thereby promoting induction of proinflammatory cytokines in these cells. 45) TRB1 is also a target of inflammatory signals, which provides a molecular rationale for the amplification of proinflammatory responses in white adipose tissue.…”
Section: Discussionmentioning
confidence: 99%
“…13) TRB1 also has a role in the ubiquitin-proteasome pathway as an adaptor protein for constitutive photomorphogenic protein 1 (COP1), thereby promoting ubiquitination and degradation of acetyl coenzyme A carboxylase (ACC) 14) and CCA AT/enhancer-binding protein (C/EBPα, C/EBPβ). 15,16) TRB1 is implicated in diseases such as cancer and myocardial infarction, and high TRB1 expression with gene amplifications is associated with acute myeloid leukemia (AML) and myelodysplastic syndrome through promotion of ERK phosphorylation and degradation of C/EBPα. 14,17,18) There is also evidence linking TRB1 to control of plasma lipid homeostasis, which suggests that this molecule may be linked to risk factors for myocardial infarction.…”
mentioning
confidence: 99%
“…It is thought TRIB1 acts to negatively regulate C/EBP proteins by acting as adaptors to recruit COP1 to C/EBP family members thereby promoting ubiquitination and degradation. Studies have shown that COP1 requires TRIB1 for its action of C/EBPα (Yoshida, et al 2013).…”
Section: Localisationmentioning
confidence: 99%
“…The G-S-P motif is present in human SNIP1 (Smad nuclear interacting protein) which functionally associates with BGR1, which interacts with the Drosophila homologue of Slbo, C/EBP transcription factors (Beausoleil, et al 2004, Kadam, et al 2000. C/EBP transcription factors have been shown to functionally and physically interact with TRIB1 promoting their degradation (Yoshida, et al 2013). Kinase-like domain TRIB1 contains a Ser/Thr kinase-like domain that is composed of some of the motifs present in catalytically active kinases such as a Lysine crucial for ATP binding whilst others are missing.…”
Section: Descriptionmentioning
confidence: 99%
“…11 In mammals, putative substrates of COP1 include transcription factors (c-Jun, ETV1, p53, C/EBPa, TORC2, and FOXO1) and enzymes (acetyl-CoA carboxylase) that are involved in tumorigenesis and metabolism. 7,[12][13][14][15][16][17][18] Because COP1 functions in many biological responses in mammalian cells, the tribbles family appears to be an adaptor protein that recruits COP1 to a specific substrate for proteasome-mediated degradation. The Trib1-COP1 ligase complex specifically targets C/EBPa for degradation in hematopoiesis, and its overexpression causes AML in mouse models.…”
Section: Introductionmentioning
confidence: 99%